Slope Design for Cost Optimization of Slope Cutting and Reinforcement (Case Study: Trans-Sumatra Toll Road Rengat Pekanbaru Section Lingkar Pekanbaru Junction Pekanbaru Sta. 205+150 - 205+725) - Prasetiyo, R Fiansyah Dwi; Mochtar, Noor Endah; Mochtar, Indra Surya B; Muliawan, Mahar (Journal of Infrastructure & Facility Asset Management, 2025)
The trans-Sumatra toll road project currently under construction is the Rengat - Pekanbaru toll road construction project, the Pekanbaru ring road section located at km 205 + 150 to km 205 + 725 (575m long). In this section, quite deep excavation work is required as well as quite wide land acquisition which causes expensive land acquisition costs. In this study, slope variations were carried out with steeper angles in order to obtain a smaller road ROW; only additional reinforcement needs to be planned so that the slope is more stable and does not cause landslides. The stability of the varying slope slopes was analyzed using an auxiliary program to obtain the safety factor for each selected slope. In conducting the analysis, the elevation of the groundwater level was varied, namely at the bottom of the excavation (conditions during the dry season), as in secondary data, and at the top of the excavation (conditions during maximum rainfall). Slope stability analysis was also carried out using the ' theory of cracked soil' approach. Slope reinforcement using ground anchors will be planned if SF <1.0; for slopes that have SF ≥ 1.0, rainwater management will be carried out without reinforcement. The excavation slope at Sta 205+400 with a slope of 1:2 and 1:3 and the groundwater level at the top of the excavation is SF = 1.73; if the analysis is carried out using the cracked soil approach, the safety factor value drops to SF = 0.68. In addition, in the alternative slope gradients, namely alternative 1 with a slope angle of 1:1 and alternative 2 with a slope angle of 2:1, the slope safety factor changes quite drastically to 0.39 in alternative 1 and 0.2 in alternative 2. The cost calculation for alternative 2 with a slope gradient of 2:1 saves excavation work of 183,136.31 m3, 34,375 m2 of land acquisition and reinforcement costs of 3,422 Ground anchor points in cracked soil conditions and groundwater elevation with existing conditions of secondary data. Cost optimization of Rp. 18,423,905,547,-